Composite large cell neuroendocrine carcinoma and adenocarcinoma of the common bile duct. Issue 1 (4th January 2006) - Sato, K; Waseda, R; Tatsuzawa, Y; Fujinaga, H; Wakabayashi, T; Ueda, Y; Katsuda, S
Abstract : Large cell neuroendocrine carcinoma (LCNEC) is a high grade type of neuroendocrine tumour with an aggressive clinical course. This report describes the first case of LCNEC combined with an adenocarcinoma component in the common bile duct. A 68 year old man presented with jaundice. Severe stenosis of the bile duct was revealed by endoscopic retrograde cholangiography, and adenocarcinoma cells were detected by brush cytology. Pancreaticoduodenectomy was performed, and the patient died of disease three months after surgery. A tumour measuring 2.0 cm in diameter was located in the intrapancreatic portion of the bile duct. Histologically, the tumour consisted of a LCNEC component and a well differentiated adenocarcinoma component. There were transitional areas between the two components. Immunohistochemically, LCNEC cells were reactive for neuroendocrine markers, but no specific hormonal expression was found. Chromogranin A positive cells were found in some areas of the adenocarcinoma component. These findings are consistent with the theory that both of the carcinoma components originated from a common pluripotent stem cell.